Fa‘āliyyah Tarĩqati Salāmiyyati Al Asābi‘ Fi Hifzi ‘Alāmāti Al-Fi‘li Al-Mādi Wa Al Amr - Zam Zam Rasidi; M. Syihabuddin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Arabic grammar (nahwu), particularly the mastery of markers of fi‘il māḍī and fi‘il amr, is essential for understanding classical Islamic texts but often poses challenges for pesantren students. The abstract nature of these markers and reliance on rote memorization lead to low comprehension and retention. To overcome this, innovative strategies are needed. One such approach is the finger-joint method, a kinesthetic mnemonic technique using finger joints as visual aids to strengthen memory and facilitate learning. This study investigates the effectiveness of the finger-joint method in improving students’ mastery of fi‘il māḍī and fi‘il amr at Pondok Pesantren Tahfizh Al-Qur’an Daarul Ihsan (DIIBS) Barito Kuala. Employing a quantitative design with a one-group pretest–posttest model, the research involved 18 Group 1 students as participants. Data were gathered through tests, observation, and documentation. The test instrument consisted of 20 validated multiple-choice items, while data analysis utilized descriptive statistics and the Paired Sample T-Test via SPSS version 25. The findings showed a significant improvement in learning outcomes. The mean pretest score of 32.78 increased to 56.39 in the posttest. Hypothesis testing yielded a Sig. (2-tailed) value of 0.000 < 0.05, leading to rejection of H₀ and acceptance of Hₐ. This confirms the significant effectiveness of the finger-joint method in enhancing mastery of fi‘il māḍī and fi‘il amr. In conclusion, the finger-joint method is effective and practical for nahwu instruction in pesantren. Besides boosting academic achievement, it creates an engaging learning experience, supporting deeper comprehension of Arabic grammar.